Metode Komunikasi Dakwah Terhadap Pembinaan Prinsip Keagamaan Jamaah Massjid Al-Munawwarah Sape Desa Naru Barat Kecamatan Sape Kabupaten Bima - Taufikurahman, Taufikurahman; Upe, Muh. Ilyas; Shamad, M. Ishaq (Universitas Muslim Indonesia, 2021)
This article discusses the Communication Method of Â Da'wah to the Guidance of Religious Principles for the Al-Munawwarah Mosque Congregation Sape, West Naru Village, Sape District, Bima Regency. Dai is the most important element as the successor of da'wah ever brought by the role model of the king Muhammad SAW. This sacred task is a challenge for a dai to improve various da'wah methods to foster religious principles. The main discussion in this thesis are: 1) how is the method of fostering the religious principles of the congregation of Al-Munawwarah Sape Mosque? 2) How can the coaching method delivered by the dais improve the quality of religious principles for the congregation? This type of research is a qualitative research with the research location at the Al-Munawwarah Sape Mosque, West Naru Village. The data collection methods used by the researcher are observation, interviews, and documentation. The sources of this research data are the Mosque Welfare Board and dai who play a role in religious development efforts. The results of the research obtained are the da'wah communication method on the guidance of the religious principles of the Al-Munawwarah Sape using the method, discussion method, Uswatun Hasanah method, and the book study method carried out by the preacher which has a significant impact and has an influence on the results of guiding principles. religious.